Atom‐probe tomography and transmission electron microscopy of the kamacite–taenite interface in the fast‐cooled Bristol IVA iron meteorite. (15th October 2017) - Rout, Surya S.; Heck, Philipp R.; Isheim, Dieter; Stephan, Thomas; Zaluzec, Nestor J.; Miller, Dean J.; Davis, Andrew M.; Seidman, David N.
Abstract: We report the first combined atom‐probe tomography (APT) and transmission electron microscopy (TEM) study of a kamacite–tetrataenite (K–T) interface region within an iron meteorite, Bristol (IVA). Ten APT nanotips were prepared from the K–T interface with focused ion beam scanning electron microscopy (FIB‐SEM) and then studied using TEM followed by APT. Near the K‐T interface, we found 3.8 ± 0.5 wt% Ni in kamacite and 53.4 ± 0.5 wt% Ni in tetrataenite. High‐Ni precipitate regions of the cloudy zone (CZ) have 50.4 ± 0.8 wt% Ni. A region near the CZ and martensite interface has <10 nm sized Ni‐rich precipitates with 38.4 ± 0.7 wt% Ni present within a low‐Ni matrix having 25.5 ± 0.6 wt% Ni. We found that Cu is predominantly concentrated in tetrataenite, whereas Co, P, and Cr are concentrated in kamacite. Phosphorus is preferentially concentrated along the K‐T interface. This study is the first precise measurement of the phase composition at high spatial resolution and in 3‐D of the K‐T interface region in a IVA iron meteorite and furthers our knowledge of the phase composition changes in a fast‐cooled iron meteorite below 400 °C. We demonstrate that APT in conjunction with TEM is a useful approach to study the major, minor, and trace elemental composition of nanoscale features within fast‐cooled iron meteorites.